2016
DOI: 10.1002/ecs2.1404
|View full text |Cite
|
Sign up to set email alerts
|

National parks in the easternUnitedStates harbor important older forest structure compared with matrix forests

Abstract: States harbor important older forest structure compared with matrix forests. Ecosphere 7(7):e01404. 10.1002/ecs2.1404Abstract. We analyzed land-cover and forest vegetation data from nearly 25,000 permanent plots distributed across 50 national parks in the eastern United States, along with the matrix around each park, to examine structural characteristics of park forests in relation to their surrounding landscape. Over 2000 of these plots are part of the National Park Service (NPS) Inventory and Monitoring Prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…While areas managed for multiple uses including resource extraction (i.e., national forests) and protected areas serve different societal purposes and, for this reason and others, are unlikely to have convergent forest structure and function, we can still learn important lessons when protected areas contain stable populations of species of conservation concern. For example, protected areas often form refuges for ecosystems containing distinctive biological features such as large old trees (Miller et al, 2016) and, therefore, they can act as blueprints for ecological restoration (BoisramĂ©, Thompson, Collins, & Stephens, 2017). Furthermore, protected areas may contain tree sizes, age structure and intact disturbance regimes (Lydersen & North, 2012) characteristic of ecologically resilient landscapes (i.e., landscapes that have the capacity to recover their ecological functioning following a disturbance) and that more closely reflect species' evolutionary environments (Moore, Covington, & FulĂ©, 1999).…”
Section: Extinction Debt and Restoration Opportunitiesmentioning
confidence: 99%
“…While areas managed for multiple uses including resource extraction (i.e., national forests) and protected areas serve different societal purposes and, for this reason and others, are unlikely to have convergent forest structure and function, we can still learn important lessons when protected areas contain stable populations of species of conservation concern. For example, protected areas often form refuges for ecosystems containing distinctive biological features such as large old trees (Miller et al, 2016) and, therefore, they can act as blueprints for ecological restoration (BoisramĂ©, Thompson, Collins, & Stephens, 2017). Furthermore, protected areas may contain tree sizes, age structure and intact disturbance regimes (Lydersen & North, 2012) characteristic of ecologically resilient landscapes (i.e., landscapes that have the capacity to recover their ecological functioning following a disturbance) and that more closely reflect species' evolutionary environments (Moore, Covington, & FulĂ©, 1999).…”
Section: Extinction Debt and Restoration Opportunitiesmentioning
confidence: 99%
“…are constrained by different policies and normative standards and manage their forests to achieve different goals. For example, federally owned National Parks in the eastern United States prohibit timber harvesting and, as a result, have distinct forest structure and more biomass than surrounding forests (Miller 2016); similarly, public forestland across all federal agencies have higher stocks of aboveground biomass as compared to privately owned land (Zheng et al 2010). Patterns of forest ownership vary at both coarse and fine scales in the United States (Butler et al 2014).…”
mentioning
confidence: 99%
“…The NPS is entrusted with stewarding a rather astounding array of natural resources, that, as reflected here, often span very broad geographic (e.g., Miller et al 2016, Rodhouse et al 2016) and temporal scales (e.g., Ketz et al 2016, Paulsen et al 2016, Roland et al 2016, and multiple levels of ecological complexity (e.g., Coletti et al 2016, Fakhraei et al 2016. The NPS is entrusted with stewarding a rather astounding array of natural resources, that, as reflected here, often span very broad geographic (e.g., Miller et al 2016, Rodhouse et al 2016) and temporal scales (e.g., Ketz et al 2016, Paulsen et al 2016, Roland et al 2016, and multiple levels of ecological complexity (e.g., Coletti et al 2016, Fakhraei et al 2016.…”
Section: Special Feature Highlightsmentioning
confidence: 99%
“…Miller et al (2016) showed that parks in the eastern United States provide significantly older forest structure and different demographic rates than forests outside of parks. Miller et al (2016) showed that parks in the eastern United States provide significantly older forest structure and different demographic rates than forests outside of parks.…”
Section: Special Feature Highlightsmentioning
confidence: 99%
See 1 more Smart Citation